Understanding Pyrrolidine Dithiocarbamate's protective effect against Cisplatin-induced toxic side effects in Rats. Issue 1 (June 2022) - Al Masri, Nasser; AlMadani, Abdullah; Hussien, Fuad; Alkhlaiwi, Ahmad Ali; Azmi, Sarfuddin
Through the examination of biochemical parameters (creatinine and BUN) and oxidative stress values (TBRAS, Catalase activity, and GSH), we have attempted to evaluate the protective effect of PDTC against toxic consequences of CIS treatment. In the study, animals (Rats Wistar) were randomly assigned to one of four groups of six animals each: untreated or treated with vehicle (group-1), treated with PDTC (group-2), treated with CIS (group-3), and treated with a combination of CIS and PDTC (group-4). In this study, two tissues were chosen to investigate oxidative stress (a toxic side effect), and these tissues were the kidney and the ileum. In CIS treatment, the level of serum creatinine and blood urea nitrogen (BUN) exponentially increased and simultaneous treatment of CIS and PDTC restored their levels. Similarly, treatment of CIS, considerably increases lipid peroxidation, i.e., TBRAS level in both tissue Kidney and intestine, however, treatment in the combination of PDTC, substantially retained their level similar to the vehicle-treated group. In contrast, Catalase activity and reduced glutathione (GSH) levels were compromised in the kidney after CIS treatment, but significantly increased in the intestinal tissue compared to the untreated group, and treatment with PDTC restored Catalase activity and GSH levels in both tissues to levels comparable to the untreated group. Thus, the study indicated that oxidative stress is caused by an increase in reactive oxygen species (ROS) or a depleted antioxidant system, or both, which ultimately result in side toxic effects toward the different organs.